Triangular modeling using Delaunay based region growing approach - Agrawal, Vandana (International Journal of Engineering and Technology, 2019)
In the present work a Delaunay based region growing algorithm is proposed to create triangulated model from the unorganized data set obtained by coordinate measuring machine (CMM).The algorithm maintains the advantages of both Delaunay based and region growing approaches. In this algorithm a data structure is created which contains the information about the edges and the vertices of all the triangles created by Delaunay triangulation. Further a region growing process is used by initiating a seed triangle. The new triangles selected from Delaunay data structure are incrementally added to the region. One of the advantage of suggested algorithm is that no post processing is required as hole filling and topological examination is done during the growing process itself. The region growing takes place more smoothly along the faces of the object when algorithm is applied by incorporating hole filling process and topological examination. Further, the holes and topological disorders like neck vertices and non-manifold surface disappeared when algorithm is applied by incorporating hole filling process and topological examination in comparison to the modelling excluding them. The triangulated model created so can be used for subsequent processes of reverse engineering like segmentation and surface fitting.Â